Glucose-Lowering and the Risk of Cardiovascular Events With Antidiabetic Therapies: A Systematic Review and Additive-Effects Network Meta-Analysis - Carvalho, Luiz Sergio Fernandes de; Nogueira, Ana Claudia Cavalcante; Bonilha, Isabella; Luchiari, Beatriz; Benchimol, Alexander; Couri, Carlos Eduardo Barra; Borges, Jairo Lins; Barreto, Joaquim; Sposito, Andrei C. (Frontiers in Cardiovascular Medicine, 2022)
Aim: To assess the impact of the HbA1c levels achieved with newer ADTs on the risk of MACE. Methods. A systematic search was performed in PubMed, Cochrane, and ClinicalTrials.gov for RCTs published up to January/2021 reporting the occurrence of MACE and all-cause mortality in individuals with T2DM, including a sample size ≥100 individuals in each study arm and follow-up ≥24 weeks. A systematic review and additive-effects network meta-analysis with random effects and a multivariate meta-regression were utilized to assess the impact of achieved HbA1c on incident MACE. Results. We included 122 RCTs with 139 treatment arms, 256,990 individuals, and 689,346 individuals-years who were randomized to an active treatment vs. control group. Therapy with SGLT2i, GLP1-RA, or pioglitazone similarly reduced the risk of MACE compared to placebo (HR 0.88 [95%CI 0.83, 0.94, p<0.001], 0.89 [95% CI 0.85, 0.94, p<0.0001], and 0.86 [95% CI 0.76, 0.98, p=0.025], respectively). The achievement of HbA1c≤7.0% in RCTs with newer ADT in the active arm was associated with an adjusted HR of 0.91 (95% CI 0.80, 0.97; p=0.039) compared with HbA1c>7.0%, without affecting all-cause mortality. Conclusions: Achieving lower glucose levels with newer ADTs is linearly associated with a reduced risk of MACEs, without affecting all-cause mortality.